(untitled) (Faridpur Medical College Journal, 2011)
Hypertension is an important independent predictor of cardiovascular disease, cerebrovascular accidents and death. The prevalence of cardiovascular diseases and hypertension is rapidly increasing in developing countries. A cross sectional study was conducted among 103 hypertensive patients during December 2009 to June 2010 in Goshair Hat Upazilla of Shariatpur District to determine the socio-demographic, clinical characteristics and status of control of hypertension in rural population. Respondents were distributed more or less equally among males and females. The mean ± SD and median age of the respondents were calculated as 59.97 ± 11.12 years, with 64% of them were included in the age group of 51 to 70 years. More than half of the respondents were housewives (51.5%), which were followed by businessmen (21.4%). Every three of five patients were over weight, while 22.3% respondents were obese. One third of the respondents were also diabetic (33%). None of the 103 patients had achieved the target for SBP (Systolic blood pressure) control (<140mm of Hg) and only 21.4% of the patients had achieved the target for DBP (Diastolic blood pressure) control (<90 mm of Hg). Again none of the diabetic hypertensive patients had achieved the target for SBP control (<130mm of Hg) and only one patient had achieved the target for DBP control (<80 mm of Hg). Overall five patients were found to have uncontrolled and severe hypertension (BP >180/110 mm of Hg), all of whom were female. From this study control of hypertension was found poor among rural hypertensive population. For effectively combating the burden of hypertension in this population, education and awareness about hypertension needs to be given priority. Key words: Hypertension; socio-demographic characteristics; rural area; control of blood pressure DOI: 10.3329/fmcj.v6i1.7402 Faridpur Med. Coll. J. 2011;6(1): 05-09